Urgensi Pendidikan Islam dalam Pembentukan Akhlak Al-Kharimah Generasi Milenial di Desa Togoliua - Adiyana Adam; Astrifani Basama; Milawati Hadilla; Idayanti Sadek (Peneliti.net, 2022)
In Islamic education, the formation of character al-kharimah, faith and piety to Allah SWT is one part of the objectives of the Islamic education curriculum. The formation of Ahlak al-karimah is very important in the context of forming the character and personality of a good Muslim according to the demands of the Qur'an and al-Hadith in order to achieve a happy and prosperous life both in this world and in the hereafter. Another fact that occurs in today's millennial generation is that they prefer to play using technology in their hands such as cellphones than chatting face-to-face with friends, family or other people, even when they are together they prefer to use their cellphones rather than talking directly to people. who is in front of him. Even worse, this situation also applies when they are dealing with their parents. When their parents say something or discuss it with them, it turns out that they prefer to fiddle with their cellphones rather than pay attention to what their parents say. The research method was carried out in a descriptive qualitative way with the results of the study concluding that the Millennial Generation in the Togoliua village mostly did not understand Islamic education so that it was necessary to provide guidance so as not to cause mistakes and moral ugliness.